2022
DOI: 10.3389/femat.2022.878308
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Order Parameter Anisotropy on the Vortex Lattice in UPt3

Abstract: We have used small-angle neutron scattering to determine the vortex lattice phase diagram in the topological superconductor UPt3 for the applied magnetic field along the crystalline c-axis. A triangular vortex lattice is observed throughout the superconducting state, but with an orientation relative to the hexagonal basal plane that changes with field and temperature. At low temperature, in the chiral B phase, the vortex lattice undergoes a non-monotonic rotation with increasing magnetic field. The rotation am… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
1
1
0
Order By: Relevance
“…( 1) is not based on an ab-initio derivation, but is instead motivated by an expression for the VL free energy obtained from Ginzburg-Landau (GL) theory 50 . As shown by Olszewski et al, this potential reproduces the experimentally observed macroscopic VL phases in MgB 2 10 and UPt 3 [11][12][13] for a suitable choice of parameters K 6 and K 12 25 . It can thus be considered a minimal model for MD simulations of the VL in superconductors with a hexagonal crystal structure.…”
Section: Methodssupporting
confidence: 74%
See 1 more Smart Citation
“…( 1) is not based on an ab-initio derivation, but is instead motivated by an expression for the VL free energy obtained from Ginzburg-Landau (GL) theory 50 . As shown by Olszewski et al, this potential reproduces the experimentally observed macroscopic VL phases in MgB 2 10 and UPt 3 [11][12][13] for a suitable choice of parameters K 6 and K 12 25 . It can thus be considered a minimal model for MD simulations of the VL in superconductors with a hexagonal crystal structure.…”
Section: Methodssupporting
confidence: 74%
“…For magnetic fields applied along the c axis of superconductors with a hexagonal crystal structure, the VL is empirically found to always have a triangular symmetry, but will often undergo continuous and sometimes even non-monotonic rotations as seen in MgB 2 and UPt 3 [11][12][13] . In addition, the VLs in these materials exhibit significant metastability when cooled or heated across equilibrium phase transitions in a constant field 11,14 .…”
Section: Introductionmentioning
confidence: 99%